(untitled) (Research, Society and Development, 2023)
Chagas disease persists as an important parasitosis that affects humanity, being classically transmitted by the feces and urine of triatomines, which are deposited on the skin during hematophagy, thus allowing the penetration of metacyclic trypomastigotes forms of the protozoan Trypanosoma cruzi. Despite being classic, the referred route of transmission has been superimposed on oral transmission, given several factors, among which the control of populations of triatomines and housing improvements, as well as the increase in food consumption, with emphasis on Amazonian fruits, to the example of açaí. Therefore, this research aimed to demonstrate and discuss the relevance of oral transmission of Chagas disease (DCO), and to investigate aspects related to this process, in order to raise possible strategies to minimize it. To this end, a retrospective cross-sectional study was carried out over a period of 10 years (2011-2020) with a quantitative approach, through the collection and processing of data available on government websites, with emphasis on DATASUS. It was observed that the oral route of transmission persists as the main form of acquisition of DCO in Brazil, with a higher incidence of cases in the North region, probably because it is a region traditionally producing and consuming Amazonian fruits, such as açaí and cupuaçu. In this sense, it is important to implement prevention methods and strategies aimed at the extractive and processing processes of Amazonian fruits and other foods potentially contaminated by triatomine excretions, as a way to minimize the negative impacts of this disease, such as the introduction or reinforcing adherence to food sterilization techniques such as blanching and high isostatic pressure - HIP.